Modification of graphene oxide by laser irradiation: a new route to enhance antibacterial activity. (9th May 2016) - Buccheri, Maria A; D'Angelo, Daniele; Scalese, Silvia; Spanò, Simon F; Filice, Simona; Fazio, Enza; Compagnini, Giuseppe; Zimbone, Massimo; Brundo, Maria V; Pecoraro, Roberta; Alba, Anna; Sinatra, Fulvia; et al.
Abstract: The antibacterial activity and possible toxicity of graphene oxide and laser-irradiated graphene oxide (iGO) were investigated. Antibacterial activity was tested on Escherichia coli and shown to be higher for GO irradiated for at least three hours, which seems to be correlated to the resulting morphology of laser-treated GO and independent of the kind and amount of oxygen functionalities. X-ray photoelectron spectroscopy, Raman spectroscopy, dynamic light scattering and scanning electron microscopy (SEM) show a reduction of the GO flakes size after visible laser irradiation, preserving considerable oxygen content and degree of hydrophilicity. SEM images of the bacteria after the exposure to the iGO flakes confirm membrane damage after interaction with the laser-modified morphology of GO. In addition, a fish embryo toxicity test on zebrafish displayed that neither mortality nor sublethal effects were caused by the different iGO solutions, even when the concentration was increased up to four times higher than the one effective in reducing the bacteria survival. The antibacterial properties and the absence of toxicity make the visible laser irradiation of GO a promising option for water purification applications.